Fenomenologia Husserla — filozofia podejrzenia czy pewności? - Łaciak, Piotr (Folia Philosophica, 2018)
The aim of the article is to question the Cartesian interpretation of Husserl’s philosophy. In that interpretation Husserl is regarded as a representative of epistemological fundamentalism characterized by searching for the foundations of cognition in the transcendental consciousness given in the absolute and adequate evidence. The thesis of this article states that the essential anonymity which Husserl ascribes to consciousness is the crucial argument for his questioning of the Cartesian myth of the self-transparency of consciousness and thus allows for regarding him as the master of suspicion in a meaning which Paul Ricoeur has endowed this concept with. According to Husserl, consciousness, at the beginning of philosophical thinking, appears to be unknown, hidden, since a human being living in a natural disposition, is immersed in anonymity and forgets about his own subjectivity. Though this anonymity may be overcome by means of phenomenological reduction, the transcendental consciousness, uncovered due to that reduction, in its deepest layers will remain anonymous and will not present itself adequately in self-reflection.